Anaerobic conditions are a major influence on Candida albicans chlamydospore formation - Williams, Shannon; Cleary, Ian; Thomas, Derek (Folia microbiologica, 2023)
Candidiasis now represents the fourth most frequent nosocomial infection both in the USA and worldwide. Candida albicans is an increasingly common threat to human health as a consequence of AIDS, steroid therapy, organ and tissue transplantation, cancer therapy, broad-spectrum antibiotics, and other immune defects. Unfortunately, these infections carry unacceptably high morbidity, mortality rates and important economic repercussions (estimated total direct cost of approximately 2 billion dollars in 1998 in US hospitals alone). This pathogen can grow both in yeast and filamentous forms and the pathogenic potential of C. albicans is intimately related to certain key processes including filamentation. Chlamydospores are considered to be a dormant form of C. albicans that remain understudied. Chlamydospores have been widely used as a diagnostic tool to separate C. albicans and C. dubliniensis from other Candida species. More recently, media have been developed that use chlamydopsore formation to separate C. albicans and C. dubliniensis from each other. Chlamydospore formation can be stimulated by hypoxic conditions but only on limited specific media types. Here, we show that anaerobic conditions are enough to drive chlamydospore formation in C. albicans on the surface of nutrient-rich agar.
Keywords: Candidiasis; Candida albicans; Candida; lidé; Anaerobiosis; anaerobióza; kultivační média; Culture Media; kandidóza; Humans